Biological and Molecular Characterization of Two Closely Related Arepaviruses and Their Antagonistic Interaction in Nicotiana benthamiana - Wang, Yaodi; Shen, Wentao; Dai, Zhaoji; Gou, Bei; Liu, Hongjun; Hu, Weiyao; Qin, Li; Li, Zengping; Tuo, Decai; Cui, Hongguang (Frontiers in Microbiology, 2021)
Previously, our group characterized two closely-related viruses from Areca catechu, areca palm necrotic ringspot virus (ANRSV) and areca palm necrotic spindle-spot virus (ANSSV). These two viruses share a distinct genomic organization of leader proteases, and represent the only two species of the newly established genus Arepavirus of the family Potyviridae. The biological features of the two viruses are largely unknown. In this study, we investigated the pathological properties, functional compatibility of viral elements, and inter-species interactions in the model plant, Nicotiana benthamiana. Using a newly obtained infectious clone of ANRSV, we showed that this virus induces more severe symptoms compared to ANSSV, and that this is related to a rapid virus multiplication in planta. A series of hybrid viruses were constructed via substitution of multiple elements in the ANRSV infectious clone with the counterparts of ANSSV. The replacement of either 5′-UTR-HCPro1-HCPro2 or CI effectively supported replication and systemic infection of ANRSV, whereas individual substitution of P3-7K, 9K-NIa, and NIb-CP-3′-UTR abolished viral infectivity. Finally, we demonstrated that ANRSV confers effective exclusion of ANSSV both in co-infection and superinfection assays. These results advance our understanding on fundamental aspects of these two distinct but closely-related arepaviruses.